Analysis Of Entrepreneurship Education And The Use Of Social Media On Interest In Entrepreneurship, Students Of The Faculty Of Economics Uki Toraja - Diane Intan (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
The purpose of this study was to find out and analyze the effect of entrepreneurship education and the use of social media on the interest in entrepreneurship of students majoring in management at the Faculty of Economics, UKI Toraja. This research is a quantitative descriptive study with a total population of 604 students. The number of samples was 241, namely students from the Faculty of Economics UKI Toraja who had programmed entrepreneurship courses. Determination of the sample using random sampling technique. To test the hypothesis used multiple linear regression. The results of the study prove that simultaneously entrepreneurship education and the use of social media have a positive and significant influence on the interest in entrepreneurship for students of the economics faculty of UKI Toraja.